Relationship of Knowledge with Compliance of Patients with Hypertension to the Use of Antihypertensive Medicines in Outstanding Installations RSUD M.M Dunda, Gorontalo Regency - Mutiara Hasan; Rita Amini Warastuti; Sarini Pani (LPPM Universitas Bina Mandiri Gorontalo, 2022)
Hypertension is a cardiovascular disease characterized by high blood pressure. Hypertension if not treated properly can cause complications. Barriers to hypertension treatment are caused by several factors, namely non-compliance and lack of knowledge. This study aims to determine the level of knowledge and adherence of patients with hypertension to the use of antihypertensive drugs in the outpatient installation of RSUD M.M. Dunda Gorontalo Regency. In this study, the author uses a cross sectional analysis research design. The population in this study were all hypertensive patients in RSUD M.M. Dunda Gorontalo Regency as many as 221 people with Non Probability Sampling technique with Purposive Sampling Technique. The independent variable is the knowledge of hypertension sufferers and the dependent variable is the adherence to taking antihypertensive drugs, the instrument in this study uses a questionnaire. Data analysis used the Spearmen Rank test with a significance level of 0.05. Based on the research, it can be seen that 36 respondents (64.3%) have sufficient knowledge and 20 (35.7%) have good knowledge, in the respondents, 28 (50.0%) adherence to taking antihypertensive drugs are not obedient, 21 (37.5%) Moderately obedient, 7 (12.5%) complied with taking medication. The results of the Chi-Square test show a probability value of p value 0.393 (p> 0.05), then H1 is rejected and H0 is accepted, meaning that there is no relationship between knowledge and adherence of patients with hypertension to the use of antihypertensive drugs in the outpatient installation of RSUD MM Dunda, Gorontalo Regency.